Risk Factors Causing Overweight and Obesity in Children and Adolescents - Putri Nabilla Rachmadini; Ervina Damayanti; Citra Yuliyanda Pardilawati; Asep Sukohar (Sean Institute, 2025)
Child and adolescent obesity is an increasing global health problem. It has long-term impacts, including an increased risk of non-communicable diseases such as diabetes, hypertension and cardiovascular disorders in adulthood. This study aims to identify risk factors that contribute to obesity in children and adolescents. The meta-analysis used was a literature review through Science Direct, Pubmed, and Google Scholar databases. A total of 59 articles were identified and 18 articles published between 2018 and 2024 that met the inclusion and exclusion criteria were included in this study. The data obtained showed that the main risk factors included unhealthy eating habits, minimal physical activity, as well as the influence of genetic factors, excessive use of electronic devices, and unsupportive social and family environments. In addition, economic and cultural factors also play an important role in influencing eating habits and physical activity. In conclusion, childhood and adolescent obesity is caused by a complex interaction between individual, environmental and social factors. Prevention efforts require a multidisciplinary approach that focuses on education, promotion of healthy lifestyles, and support from the social environment .